Future-proofing sustainable cooling demand - Toby Peters; Leylan Sayin (Asian Development Bank Institute (ADBI), 2022)
The global cooling demand is expected to grow substantially during the 21st century. Apart from the increasing temperatures due to climate change, this demand will also be driven by a set of demographic characteristics, including population growth, urbanization, increasing incomes, social policies and commitments, and improved access to electricity. Indeed, space cooling demand could increase by 300% globally by 2050 and is concentrated in the hotter regions of the world with growing populations and incomes. However, this demand will likely contribute to its own growth if delivered along conventional patterns, significantly increasing GHG emissions due to high energy consumption as well as leakage of refrigerants, and hence compromising many of our economic, environmental, social, and political goals, targets, and commitments. This paper presents a system-level approach to cooling provision in buildings and urban environments, while also highlighting the need for a holistic consideration of the cooling demand across other sectors (e.g., transport), to ensure sustainability and resilience throughout the life cycle of buildings and wider infrastructure. It aims to drive a new system level thinking in key areas - how we mitigate, make, store, move, manage, finance, and regulate cold - to meet current and future cooling needs efficiently, sustainably, and affordably, while building resilience in line with the ambitions of the Paris Agreement, the Kigali Amendment to the Montreal Protocol, and the UN Sustainable Development Goals.
Keywords: Q2; Q4; 330; cooling demand; urban environment; global warming